Immune-Mediated Cytotoxicity in Inflammatory Bowel Disease - Stephan R Targan; Richard L Deem; Fergus Shanahan (Canadian Journal of Gastroenterology)
Thirty years of research on the role of immune-mediated cytotoxic activity in the tissue injury of inflammatory bowel disease (IBD) has yielded only inconclusive data on the relevance of cytotoxic mechanisms. Two hypotheses have been advanced. One is that the destruction of target cells is mediated by direct recognition of target antigens by cytotoxic cells which in turn triggers lysis. Another hypothesis is that lysis occurs via an indirect bystander mechanism in which cells do not recognize a specific antigen on the target, but upon nonspecific activation release cytokines which are capable of lysing the target. The authors have investigated both hypotheses and studied the role of cytotoxic T cells and cytotoxic rectors released from activated T cells in the destruction of epithelial cells. Elevated levels of cytotoxic T cells were found in peripheral blood lymphocytes of patients with IBD, particularly Crohn's disease. The cytotoxic T cells were contained within the Leu 7+, CD8+ T cell subset and were detected using anti-CD3-triggered lysis. Increased cytotoxic T cell activity was also present within inflamed mucosa of patients with both Crohn's disease and ulcerative colitis. The specific targets of this activity have yet to be determined. Activation of mucosal T cells by antibodies to the T cell receptor (anti-CD3) in organ culture of normal fetal jejunum induces an enteropathy characterized by villous atrophy and crypt cell hyperplasia. This same change is seen near aphthous ulcers in patients with Crohn's disease. Soluble cytokines produced by T cells might be responsible for the mucosa! damage observed in these two models of mucosal injury. The goal of this study was to establish in vitro if cytotoxic cytokines can be released by triggering isolated colonic T cells, and what cytokine interactions are required for killing of colonic epithelial cells. These results demonstrate that human lamina propria lymphocyte T cells, triggered by addition of anti-CD3 and target cells, produce tumour necrosis factor-alpha and interferon-gamma, both of which are required for optimal killing of HT-29. Simultaneous release of these cytokines in the vicinity of epithelial cells during immune responses could play an important role in mucosal damage in IBD. The development of animal models and long term cultures of epithelial cells will allow many advances in research of the role of immune-mediated cytotoxicity in IBD.